2009
DOI: 10.1104/pp.109.146985
|View full text |Cite
|
Sign up to set email alerts
|

DkMyb4 Is a Myb Transcription Factor Involved in Proanthocyanidin Biosynthesis in Persimmon Fruit

Abstract: Proanthocyanidins (PAs) are secondary metabolites that contribute to the protection of the plant and also to the taste of the fruit, mainly through astringency. Persimmon (Diospyros kaki) is unique in being able to accumulate abundant PAs in the fruit flesh. Fruits of the nonastringent (NA)-type mutants lose their ability to produce PA at an early stage of fruit development, while those of the normal astringent (A) type remain rich in PA until fully ripened. The expression of many PA pathway genes was coincide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
227
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(251 citation statements)
references
References 94 publications
(159 reference statements)
12
227
0
5
Order By: Relevance
“…S3, Bogs et al, 2007;Akagi et al, 2009b). This suggests a function for VcMYBPA1 in blueberry PA synthesis.…”
Section: Identification Of Genes For Blueberry Flavonoid Biosynthesismentioning
confidence: 90%
See 1 more Smart Citation
“…S3, Bogs et al, 2007;Akagi et al, 2009b). This suggests a function for VcMYBPA1 in blueberry PA synthesis.…”
Section: Identification Of Genes For Blueberry Flavonoid Biosynthesismentioning
confidence: 90%
“…In grape fruit development, VvMYBA1 was shown to control anthocyanin accumulation (Kobayashi et al, 2002), while two other MYBs (VvMYBPA1 and VvMYBPA2) specifically regulate grape PA synthesis (Bogs et al, 2007;Terrier et al, 2009). PA-specific MYB regulators have also been recently described from persimmon (Diospyros kaki; Akagi et al, 2009bAkagi et al, , 2010, fruit with unusually high PA levels. Therefore, there is a need to extend studies of flavonoid gene regulation to other species of fruit.…”
mentioning
confidence: 99%
“…A second type of PA MYB regulator was defined by the discovery of VvMYBPA1 from grapevine (Bogs et al, 2007). Orthologs of this MYB were subsequently described in other species (Akagi et al, 2009). These PA MYBs appear to act in parallel as well as in tandem with the TT2-type PA MYBs; in grapevine, both PA MYBs regulate flavonoid promoters directly, but VvMYBPA2 overexpression also induces transcripts of VvMYBPA1 (Terrier et al, 2009).…”
mentioning
confidence: 99%
“…On the other hand, mRNA profiling provides some clues that coordinate reduction in the expression of the PA and shikimate pathway genes in NA-type fruits is involved in the substantial reduction of PA content (Akagi et al, 2009a). It has been suggested that NA-type fruitspecific down-regulation of DkMyb4, which is a Myb TF regulating PA and shikimate pathway genes, may reduce the expression of these genes, with a corresponding reduction in PA content in NA-type fruits (Akagi et al, 2009b). In addition, low temperatures affect the phenological expression of DkMyb4 and the resultant PA accumulation in NA-type cultivars, particularly in the early developmental stage, accompanied by a significant increase in ABA concentration, although this was not observed in the A-type cultivar (Akagi et al, 2011).…”
mentioning
confidence: 99%
“…Wild-type astringent-type (A-type) persimmon fruit accumulates PAs for a long term during its developmental stages, which ranges from the stage before full anthesis (April in Japan) to before the mature stage (August in Japan; Akagi et al, 2009a). In fruits with a spontaneous mutant phenotype, PA accumulation is terminated at an early fruit development stage and astringency is not expressed (Ikegami et al, 2005;Akagi et al, 2009b). This mutant nonastringent (NA) phenotype is also called the pollination constant NA type (Yonemori et al, 2000).…”
mentioning
confidence: 99%